Functional disorders of the gastrointestinal tract and their dietetic correction in infants - A.O. Yefanova; N.V. Mishina (Zaslavsky O.Yu., 2017)
Background. In 60-70 % of cases of visiting a doctor, the leading complaints from parents, who have children of the first months of life, are symptoms of discomfort from the infant's gastrointestinal tract: regurgitation, intestinal colic, diarrhea, constipation, which in most cases are not associated with organic changes and arise in apparently healthy children, without causing significant changes in their health status. The most frequent manifestations of functional disorders of the gastrointestinal tract include regurgitation - passive reflux of a small amount of gastric contents into the pharynx, the oral cavity and outwards. The tendency to regurgitation, accor-ding to various authors, is observed in 20-85 % of apparently healthy infants, and in 47 % of them, it has a persistent nature. The aim of the study: to evaluate the clinical efficiency of antireflux mixture, in which non-digestible polysaccharides - locust bean gum are used as a thickening agent. Materials and methods. The study group consisted of 32 children aged 1 to 12 months with regurgitation. The intensity of regurgitation was assessed in points according to a specially developed and mo-dified scale (G. Vandenplas icnibali, 1993; Shadryn O., 2010). The main group included 20 children, who received antireflux mixture, as a thickening agent, locust bean gum was used; the comparison group - 12 infants, who received antireflux mixture, as a thickening agent, starch was used. Attention was also paid to the "therapeutic position" during feeding: the child's semi-vertical position during feeding, keeping the child in a vertical position after feeding for at least 10 minutes. Results. The control of the efficiency of the resulting mixtures was monitored by a comparative analysis of the dynamics of complaints and objective data. After 10 days of "treatment" by nutrition and position, in the main group 5 children (25 %) did not have regurgitations; in 13 children (65 %), the volume and frequency of regurgitations decreased throughout the day; in 2 patients (10 %), the volume and frequency of regurgitation remained unchanged. In the comparison group, no regurgitation was observed in 2 (16.7 %) infants, the volume and frequency of regurgitation decreased in 7 (58.2 %), the vo-lume and frequency of regurgitation remained unchanged in 3 (25.1 %) children. Conclusions. Thus, the antireflux effect of mixtures, in which locust bean gum is used as a thickening agent, starts in earlier terms and is more significant.